Contra-Directional Expression of Serum Homocysteine and Uric Acid as Important Biomarkers of Multiple System Atrophy Severity: A Cross-Sectional Study - Chen, Dan; Wei, Xiaobo; Zou, Jing; Wang, Rui; Liu, Xu; Xu, Xiaofeng; Lu, Jianjun; Wang, Zhanhang; Tang, Beisha; Wang, Brian; Jin, Kunlin; Wang, Qing (Frontiers in Cellular Neuroscience, 2015)
Highlights Serum Hcy was higher in MSA patients when compared to healthy subjects, particularly in male patients. Serum UA was lower in MSA patients when compared healthy subjects, particularly in male patients. Serum Hcy levels were significantly positively correlated with the severity of MSA. The ROC curve for the combination of Hcy and UA showed potential diagnostic value in discriminating MSA from healthy subjects. Aim There is evidence suggesting that inflammatory responses play a critical role in the pathogenesis of multiple system atrophy (MSA). Whether inflammatory mediators can be used as reliable biomarkers to detect the severity and progression of MSA remains largely unknown. Methods We performed a cross-sectional study that included 47 patients with MSA and 50 healthy age-matched controls. Serum levels of homocysteine (Hcy), uric acid (UA), and C-reactive protein (CRP) were measured. These levels positively correlated with the severity of MSA, based on both motor and non-motor symptoms. Several scales were used to rate the severity of MSA, including the Unified multiple system atrophy rating scale, Parkinson’s disease sleep scale, Non-motor Symptoms Scale, the Schwab & England activities of daily living scale, Webster Scale, modified Hoehn and Yahr staging scale, and the Mini-Mental State Examination. Receiver operating characteristic (ROC) curves was applied to map the diagnostic accuracy of MSA against healthy subjects. Results Compared with healthy subjects, we found that serum Hcy was higher, UA was lower, and CRP levels were unchanged in MSA patients. These findings were especially prominent in male patients. No significant differences of serum Hcy and UA were observed between patients of MSA and PD. Interestingly, there was a significant correlation between Hcy levels and MSA severity such as movement dysfunction, declined cognition, and cardiovascular symptoms. Additionally, the ROC curve for the combination of Hcy and UA (AUC 0.736) showed potential diagnostic value in discriminating MSA from healthy subjects. Conclusion Our findings suggest that the inflammatory mediators Hcy and UA may play important roles in the pathogenesis of MSA. The measurement of serum Hcy and UA levels could then be a useful tool to accurately distinguish MSA from healthy subjects.